Proceedings of the 2nd International Conference on Digital Interactive Media in Entertainment and Arts 2007
DOI: 10.1145/1306813.1306843
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Malaysian students as gamers

Abstract: Computer games are very popular among children, teenager as well as adults. For that matter, computer games should be exploited as medium of teaching and learning. We intended to investigate the possibilities of exploring the idea of adapting computer games for Science learning in class. However, we first need to understand the background and experiences among the users in order to study how computer games might benefit them in learning. 341 students from Selangor Darul Ehsan, Malaysia were involved in this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 7 publications
0
9
0
1
Order By: Relevance
“…Digital games, an interactive technology within the multimedia learning environment, could foster an effect learning process, especially among young learners. Latif (2007) mentions that digital games, such as video or computer games, are widely accepted among children and teenagers. Recently, digital games have been used in an area called educational games.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital games, an interactive technology within the multimedia learning environment, could foster an effect learning process, especially among young learners. Latif (2007) mentions that digital games, such as video or computer games, are widely accepted among children and teenagers. Recently, digital games have been used in an area called educational games.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other studies of integrating information technology into teaching have also suggested an increase in teachers' positive attitudes toward applying DGBL in instruction. as, for example, Latif (2007) points out that digital games are positively accepted among children and teenagers. Additionally, implementing digital games in education enables students to easily absorb content knowledge through its role plays (Zhi and Zhenhong, 2008;Zin et al, 2009).…”
Section: Conclusion and Suggestionsmentioning
confidence: 99%
“…Diperkuat oleh penelitian yang mengungkap bahwa pembelajaran dengan menggunakan media pembelajaran DBGL dalam hal ini menggunakan media game dan video game dapat meningkatkan motivasi belajar dan keterampilan siswa. Dengan memperhatikan pengembangan untuk memperkaya konten pembelajaran dan kemudahan penggunaan untuk meningkatkan niat siswa untuk menggunakan, motivasi belajar, dan efektivitas belajar (Cheng et al, 2013;Latif., 2007). Penelitian Latif.…”
Section: Pendahuluanunclassified
“…Thus, it is worthwhile to explore Malaysian students', teachers' and parents' views for potential use of digital games in learning mathematics. Though some earlier studies have been conducted in Malaysia [29], [30], most were related to quantitative data or game development and there is lack of qualitative research such as through in-depth personal interviewing. Furthermore, as technologies change rapidly, so does the mind-set of people.…”
Section: Learning With Educational Gamesmentioning
confidence: 99%